2008
DOI: 10.1097/olq.0b013e31816d1f6d
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Aspects of Screening Men for Chlamydia trachomatis in the New Millennium

Abstract: Screening more men with NAAT assays may provide the possibility of reducing the overall burden of chlamydia in both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 69 publications
0
28
0
4
Order By: Relevance
“…For C. trachomatis and N. gonorrhoeae, there was no statistical difference in test sensitivity for men or women for any sample type when participants were stratified based on symptoms. Although C. trachomatis sensitivity for urine, as the recommended sample of choice for testing men, was slightly lower for symptomatic men (96.1%) than for asymptomatic men (100%), the difference was not statistically significant (2,14). For females, although N. gonorrhoeae sensitivity for female urine was slightly lower for asymptomatic women (91.7%) than for symptomatic women (100%), the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 64%
“…For C. trachomatis and N. gonorrhoeae, there was no statistical difference in test sensitivity for men or women for any sample type when participants were stratified based on symptoms. Although C. trachomatis sensitivity for urine, as the recommended sample of choice for testing men, was slightly lower for symptomatic men (96.1%) than for asymptomatic men (100%), the difference was not statistically significant (2,14). For females, although N. gonorrhoeae sensitivity for female urine was slightly lower for asymptomatic women (91.7%) than for symptomatic women (100%), the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 64%
“…Anche la positività a M. genitalium, che è del 1.75%, è in accordo con quanto riportato in letteratura (5,34,36,39,43). L'inserimento in routine dell'estrazione automatica del DNA con o senza pretrattamento del campione ha permesso ai "nuovi" test NAATs di essere impiegati anche in campioni alternativi al tampone cervicale o uretrale quali liquido spermatico e soprattutto urine, matrice biologica di elezione per lo screening soprattutto nell'uomo (11,17). Numerosi sono infatti gli studi condotti sulla tipologia di matrici su cui ricercare i diversi patogeni e la maggior parte riguardano la ricerca di C. trachomatis sulle urine (16).…”
Section: Discussioneunclassified
“…Ad esempio, nei maschi, si osserva una positività a C. trachomatis del 23.58% nel tampone uretrale, comparabile con la positività riscontrata nel liquido seminale (17.3%), mentre la positività nelle urine è solo del 5.56% (tabella 4). Questo dato non supporta i numerosi lavori in letteratura che riportano le urine come la matrice più indicata per effettuare gli screening nei maschi con una sensibilità dell'85-95% (11,17). Inoltre, nello studio MST2, tutta la messa a punto della fase di prelievo ed estrazione è stata settata confrontando la cellularità/prelievo utilizzando la quantificazione di un gene umano mediante Real-Time PCR.…”
Section: Discussioneunclassified
“…This increase in detection of positive infections from screening assays must not be overlooked in assessing the utility of outreach screening programs. When NAATs were first introduced, it was shown that they could be used to test first-catch urine (FCU) specimens from men and that the performance profiles were very similar to those seen with urethral swabs (5), and now, FCU is considered the specimen of choice for testing men for chlamydia (12). Shortly after, FCU specimens from females, when tested by NAATs, were shown to have performance profiles similar to those reported for endocervical swab specimens (4).…”
Section: Discussionmentioning
confidence: 99%